New data on millipedes of the family Julidae (Diplopoda, Julida) from Altai, Siberia - Mikhaljova, Elena V.; Nefediev, Pavel S.; Nefedieva, Julia S. (Zootaxa, 2007)
Sibiriulus altaicus Guli…ka, 1972 is redescribed based upon topotype material. The species Megaphyllum sjaelandicum (Meinert, 1868) is recorded in the fauna of Siberia for the first time. Remarks are provided for the two species encountered and Sibiriulus multinicus Mikhaljova, 2001, including notes on the variation of two latter species. All three species of the genus Sibiriulus Guli…ka, 1963 are keyed.